Data expansion: the potential of grey literature for understanding floods - S. Uhlemann; R. Bertelmann; B. Merz (Hydrology and Earth System Sciences, 2013)
Sophisticated methods have been developed and become standard in analysing floods as well as for assessing flood risk. However, increasingly critique of the current standards and scientific practice can be found both in the flood hydrology community as well as in the risk community who argue that the considerable amount of information already available on natural disasters has not been adequately deployed and brought to effective use. We describe this phenomenon as a failure to synthesize knowledge that results from barriers and ignorance in awareness, use and management of the entire spectrum of relevant content, that is, data, information and knowledge. In this paper we argue that the scientific community in flood risk research ignores event-specific analysis and documentations as another source of data. We present results from a systematic search that includes an intensive study on sources and ways of information dissemination of flood-relevant publications. We obtain 186 documents that contain information on the sources, pathways, receptors and/or consequences for any of the 40 strongest trans-basin floods in Germany in the period 1952–2002. This study therefore provides the most comprehensive metadata collection of flood documentations for the considered geographical space and period. A total of 87.5% of all events have been documented, and especially the most severe floods have received extensive coverage. Only 30% of the material has been produced in the scientific/academic environment, and the majority of all documents (about 80%) can be considered grey literature (i.e. literature not controlled by commercial publishers). Therefore, ignoring grey sources in flood research also means ignoring the largest part of knowledge available on single flood events (in Germany). Further, the results of this study underpin the rapid changes in information dissemination of flood event literature over the last decade. We discuss the options and obstacles of incorporating this data into the knowledge-building process in light of the current technological developments and international, interdisciplinary debates for data curation.